2021
DOI: 10.1186/s12967-021-02700-0
|View full text |Cite
|
Sign up to set email alerts
|

Distinct osmoregulatory responses to sodium loading in patients with altered glycosaminoglycan structure: a randomized cross-over trial

Abstract: Background By binding to negatively charged polysaccharides called glycosaminoglycans, sodium can be stored in the body—particularly in the skin—without concurrent water retention. Concordantly, individuals with changed glycosaminoglycan structure (e.g. type 1 diabetes (DM1) and hereditary multiple exostosis (HME) patients) may have altered sodium and water homeostasis. Methods We investigated responses to acute (30-min infusion) and chronic (1-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…This might indicate that an adequate response of extracellular HS increase – allowing increased interstitial tissue sodium accumulation– is necessary to protect ICFV increase. This is in agreement with our previous study, in which we showed that in response to HSD healthy controls showed dermal HS modification, whilst HS modification was absent in HME patients [ 27 ]. Besides the skin also the endothelial surface layer, a thin dynamic HS-rich layer covering endothelial cells, has been identified as an important compartment for sodium accumulation and sodium balance [ [41] , [42] , [43] ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This might indicate that an adequate response of extracellular HS increase – allowing increased interstitial tissue sodium accumulation– is necessary to protect ICFV increase. This is in agreement with our previous study, in which we showed that in response to HSD healthy controls showed dermal HS modification, whilst HS modification was absent in HME patients [ 27 ]. Besides the skin also the endothelial surface layer, a thin dynamic HS-rich layer covering endothelial cells, has been identified as an important compartment for sodium accumulation and sodium balance [ [41] , [42] , [43] ].…”
Section: Discussionsupporting
confidence: 94%
“…On day eight of our intervention a new steady state in sodium and water balance is expected to be achieved [ 45 ]. Furthermore, previous studies showed significant tissue remodeling and local osmoregulatory responses after one week of HSD [ [27] , [46] ]. However, certain limitations need to be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All three groups exhibited as a response to high salt intake an increase in the expression of nuclear factor of activated T-cells 5 (NFAT5), which is a transcription factor of cellular response to hypertonic states. Healthy subjects had an increase of skin heparan sulfate, HME patients demonstrated an increase in skin dermatan sulfate rather than heparan sulfate, while patients with type 1 diabetes mellitus had no change in their skin proteoglycans after chronic dietary sodium loading and exhibited a rise in [Na] S significantly higher than the control or HME groups after infusion of the same load of hypertonic saline ( 118 ). One other issue that will need investigation consists of what portion of intracellular potassium that is osmotically inactive ( 119 ) is involved in exchanges with the osmotically active part and participates in the determination of [Na] SW during acute changes of the fraction (TBNa + TBK)/TBW.…”
Section: Reviewmentioning
confidence: 99%
“…Previous literature on salt sensitivity regarded body salt balance in terms of the traditional isoosmolar sodium distribution, including the intravascular, interstitial, and intracellular compartments. However, recent studies showed that Na + may accumulate in the interstitium without commensurate water retention but in association with glycosaminoglycans instead ( Titze et al, 2004 ; Wenstedt et al, 2021 ). Whether this Na + is or is not hyperosmolar is controversial ( Rossitto et al, 2020 ), but irrelevant in terms of activation of immune cells, which is due to the Na + concentration, not to its osmolality ( Barbaro et al, 2017 ).…”
Section: Pathogenesis Of Salt Sensitivitymentioning
confidence: 99%